Does the Letter Matter (and for Everyone)? - Quasi-experimental Evidence on the Effects of Home Invitation on Mammography Uptake - Vincenzo Carrieri; Ansgar Wuebker (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2014)
We exploit regional variation in the availability of breast cancer screening policies and variations in age eligibility criteria across European regions to estimate the causal effect of home invitation on mammography uptake. We link administrative public data about regional breast cancer screening policies from various sources to individual Survey of Health Ageing and Retirement in Europe (SHARE) data. We find that home invitation increases mammography uptakes by almost 20 percentage points. At the same time, we find that home invitation reduces education-related inequalities but increases gradient in the use related to cognitive functions. In addition, significant effects on mammography use are found only when at least 50 per cent of the population is reached by the home invitation. Our results suggest that an exogenous informational shock affects preventive decisions especially among less informed individuals but the effectiveness of invitation is strongly reduced for women who are less able to process information. – – In diesem Papier nutzen wir regionale Unterschiede im Zugang zu Brustkrebs-Screening-Programmen sowie regionale Unterschiede in den altersspezifischen Teilnahmebedingungen, um den kausalen Effekt von schriftlichen Einladungen auf die Teilnahme an Mammographie-Screening-Programmen zu untersuchen. Hierzu werden administrative regionale Daten zu Brustkrebs-Screening-Programmen herangezogen und mit Individualdaten des Survey of Health Ageing and Retirement (SHARE) verknüpft. Wir finden heraus, dass die Einladung zum Screening die Teilnahme am Screening um fast 20 Prozentpunkte erhöht. Gleichzeitig reduziert die Einladung zum Screening bildungsbezogene Ungleichheiten in der Inanspruchnahme, jedoch erhöht sie kognitiv bezogene Ungleichheiten. Signifikante Effekte auf die Mammographieteilnahme werden nur gefunden, wenn mindestens 50 Prozent der Bevölkerung eine Einladung erhält. Unsere Ergebnisse lassen schlussfolgern, dass ein durch die schriftliche Einladung ausgelöster exogener Informationsschock einen starken Einfluss auf Präventionsentscheidungen hat. Diese Schlussfolgerung gilt insbesondere für weniger informierte Personen. Demgegenüber ist die Einladung zum Screening nicht so effektiv, wenn die Frauen weniger in der Lage sind Informationen zu verarbeiten.
Keywords: C10; I11; I14; I18; 330; home invitation; preventive health care; quasi-experiment